How does servant leadership influence managerial performance through public service motivation? - Rifa'i, Ahmad; Tan, Syamsurijal; Edward, Edward; Adriani, Zulfina (Asean International Journal of Business, 2022)
Purpose – This paper trying to test whether public service motivation is able to mediate the influence of servant leadership on managerial performance Methodology/approach – This research using quantitative methods. Data processing and hypothesis testing using WarPLS version 7.0. This research was conducted at the Government of Indragiri Hilir Regency, Riau Province, Indonesia. The sampling technique used is probability sampling with proportionate stratified random sampling. The sample was calculated using Herry King's Nomogram Table with an error rate of 5% where 135 respondents were selected. Findings – It was found that. Public Service Motivation is able to mediate the influence of servant leadership on managerial performance. The direct influence of Servant leadership on public service motivation is greater than the direct influence of servant leadership on managerial performance, the effect of public service motivation on managerial performance is the lowest. Novelty/value – Because public service motivation has become an important factor that is able to mediate the influence of servant leadership on managerial performance, it is very important to understand how to maintain managerial performance by looking at indicators of public service motivation.